Pengaruh Kecepatan Angin, Kelembapan dan Suhu Udara terhadap konsentrasi SO2 Ambien dan Pemetaan SO2 Amben di Sekitar PT. Kawasan Industri Medan - Chandra Iramawati; Muhammad Turmuzi; Isra' Suryati; Lies Setyowati; Eka Lestari Mahyuni (Universitas Andalas, 2018)
This study aims to determine the effect of wind speed, humidity and air temperature on the concentration of SO2 in ambient air around PT. Medan Industrial Area (KIM) and to find out the description of SO2 concentration mapping around KIM. This study was limited to KIM Phase I and II and sampling was carried out at 6 (six) points. The results obtained were the lowest SO2 concentration of 58.63 µg / m3 and the highest concentration was 112.91 µg / m3. Based on the linear regression test, the result is that the higher the wind speed, the concentration of SO2 in the area around KIM is lower and 15.1% SO2 concentration is influenced by wind speed. The higher the humidity of the air, the concentration of SO2 in the area around KIM is lower and 26% of the concentration of SO2 is influenced by humidity. The higher the air temperature, the higher the concentration of SO2 in the area around the KIM and 68.5% the concentration of SO2 is influenced by air temperature. Based on the results of mapping using the Surfer 11 version, the results obtained in the morning the highest SO2 concentration was in the southern part of KIM and the lowest SO2 concentration was in the northwestern part of KIM. During the day, the highest SO2 concentration was in the eastern part of the KIM and the lowest SO2 concentration was in the northwestern part of KIM.